Interspecific variation in hatching success among three sea duck species at one breeding site in the Baltic Sea - Liljebäck, Niklas; Sørensen, Iben H.; Haas, Fredrik; Sterup, Jacob; Stålnäbb, Adam; Månsson, Johan (Wildfowl, 2025)
Understanding variation in survival and reproduction is key for conservation and management of bird populations. By compiling and analysing data on hatching success (i.e. proportion of nests with at least one hatched egg) from Common Eider Somateria m. mollissima, Velvet Scoter Melanitta fusca and Red-breasted Merganser Mergus serrator, all breeding on a single island in the Baltic Sea, we demonstrate that species-specific variation can be distinct even when nests are found in the same habitat on a relatively small study site. A total of 3,316 nests was found, and hatching success was determined for 2,890 nests during a four-year study period (2021–2024). Both Common Eider and Velvet Scoter exhibited considerable interannual variation in hatching success. Hatching success for Common Eider was highest in the two last years, but in the first two years for Velvet Scoter. Red-breasted Merganser showed more stable and generally higher hatching success than the other two species. Lack of covariation between species over the years indicates that species-specific traits such as phenology and behaviour (e.g. defence-mechanisms to avoid nest predation) may override other local factors influencing breeding success. Our results suggest that knowledge of annual variation in hatching success cannot be applied to other closely related species, even when those species are found breeding in the same area and habitat and may even share nesting sites.